How Do International Tourists Choose Vegetarian Restaurant? A Thematic Analysis of TripAdvisor Reviews - Herjanto, Halimin; Dengub, Sofiya; Ryerson, James (ASEAN Journal on Hospitality and Tourism, 2025)
Customer satisfaction is the mantra for successful and sustainable vegetarian restaurants. However, the existing literature has failed to provide a comprehensive taxonomy of this phenomenon because studies have primarily been conducted in the Western world, focusing on domestic customers, overlooking Asian contexts, and adopting the perspective of international tourists traveling to these regions. Gaining insights from the Asian context, specifically from international tourists who travel to Indonesia, may offer a better understanding of such a phenomenon. Online comments on the TripAdvisor website were analyzed, and the findings suggest that nine themes (price, entertainment, setting, surprise factors, food, service, facility, location, and staff) are responsible for Vegetarian restaurant customer satisfaction.